The Seed Sector Development: Experiences in South Sudan - Yuga, M. E; Miteng, J. A (European Journal of Applied Sciences, 2024)
Agriculture accounts for 15% of Gross Domestic Product (GDP) and provides 78% of the country’s employment in South Sudan. Even though South Sudan produces a large variety of agricultural commodities for local consumption, food insecurity is dire, with over half of its population needing food assistance, from World Food Program (WFP) and other food distributing organizations in the country. Despite the broad production base, limited research and adoption of new technology has kept crop yields at its lowest compared to its peers in the region. The poorly developed seed systems have exacerbated these crises because smallholder farmers are unable to access quality seeds on a sustainable basis to increase food production. This review was carried out using secondary sources of information including reviews of literature and reports from government and humanitarian organizations. This review of the seed sector provides insight into the seed systems, progress made, bottlenecks and ways forward to ensure a functional seed system in South Sudan. To ensure a functional seed system, the Ministry of Agriculture and Food Security (MAFS) and stakeholders should review and update the Seed Act then passed into Law. In addition, the seed certification agency should be established and supported with resources to initiate seed quality control in the country. Integration of the formal and the informal seed sector is recommended, the capacity of the public and private seed actors should be enhanced to ensure competitiveness of seed sector. Establishment of a commercial, sustainable, and adaptive agriculture sector in South Sudan requires strengthening the formal and the informal seed sector, so that smallholder farmers can access high quality seeds. The food aid and other humanitarian organizations should shift from humanitarian support to agricultural development to ensure sustainable growth of South Sudan’s seed sector.